TRAINING FOR MAKING FLOOR CLEANER (CARBOL) ON BUSINESS GROUP IN SUKONOLO VILLAGE – KECAMATAN BULULAWANG – KABUPATEN MALANG - Prayitno Prayitno; Bambang Widiono; Anang Takwanto (P3M Politeknik Negeri Malang, 2022)
The